Synthesize and Characterization of Ca Substituted Co-Zn Ferrites by Micro-Emulsion Technique - Mehboob, Zeshan; Shifa, Muhammad Shahzad; Shahia, Humaira Akhtar; Muhammad Hashim (Journal of Materials and Physical Sciences, 2020)
Co-Zn ferrites have great magneto-striction, high corrosion resistivity and excellent chemical stability. We can control the ferromagnetic properties and paramagnetic properties of Co-Zn ferrites by changing its particle distribution and particle size. There are different types of techniques are available to synthesis Co-Zn ferrites like co-precipitation, sol gel and auto-combustion method etc. In this research, we will synthesize Co-Zn ferrites by micro-emulsion technique and substitute Ca in it with different composition. XRD results showed that samples were in single phase ferrite. Particle size was between the ranges of 34-14nm. Average lattice constant were 8.11-8.18Ao. FT-IR conform the results obtained by XRD. SEM conform the morphology of the samples and its grain size. Grain size decreased with increased of the concentration of Ca in Co0.6-x-Zn0.CaxFe2O4. TGA results were found in agreement with previous literatures